PENGARUH SKEPTISME PROFESIONAL, PENGALAMAN DAN FEE AUDIT TERHADAP KUALITAS AUDIT - Noviani Saputri; Nugraeni Nugraeni (LPPM Universitas Trunojoyo Madura, 2013)
Public accounting is a profession under difficult conditions. Accountants must have professional ethics, but on the other hand also had to face the pressure of clients in a variety of decision-making auditors. If the auditor is not able to resist pressure from clients, the competency of auditors has been reduced and can affect the quality of the audit. This study aims to prove that professional skepticism, experience, influence audit fees on audit quality. The data used in this study is primary data obtained after distributing questionnaires. The samples used were 44 respondents that auditors found on 6 KAP in Yogyakarta. Data analysis was performed using SPSS for Windows Release 19.0. research hypotheses using multiple regression analysis, after testing the classical assumptions. Based on the result of this study concluded that professional skepticism, experience, influence audit fees on audit quality.